Odpowiedź:
[tex]a)\ \ 2\frac{1}{7}+\frac{3}{7}=2\frac{4}{7}\\\\b)\ \ 5\frac{4}{9}+\frac{3}{9}=5\frac{7}{9}\\\\c)\ \ 1\frac{5}{11}+1\frac{3}{11}=2\frac{8}{11}\\\\d)\ \ 1\frac{3}{5}+1\frac{4}{5}=2\frac{7}{5}=3\frac{2}{5}\\\\e)\ \ 3\frac{9}{15}+2\frac{11}{15}=5\frac{20}{15}=6\frac{5}{15}=6\frac{1}{3}\\\\f)\ \ 1\frac{5}{6}+1\frac{5}{6}=2\frac{10}{6}=3\frac{4}{6}=3\frac{2}{3}\\\\g)\ \ 3\frac{5}{8}+7\frac{5}{8}=10\frac{10}{8}=11\frac{2}{8}=11\frac{1}{4}[/tex]
[tex]h)\ \ 3\frac{9}{14}+11\frac{11}{14}=14\frac{20}{14}=15\frac{6}{14}=15\frac{3}{7}[/tex]